A Magnetic TiO2/PKSAC/Fe3O4 Composite with Enhanced Photocatalysis and Adsorption for the Concurrent Removal of Heavy Metals - Mohamad Azim, Abdullah (Faculty of Resource Science and Technology, 2022)
An effective material to assist in the removal of heavy metal pollutants in the water system is necessary, as they persist for a long time and pose danger to the environment. A novel multifarious TiO2/PKSAC/Fe3O4 composite material with combined adsorption, photocatalytic and magnetic properties was successfully synthesized and applied for the simultaneous removal of mixed heavy metal ions, Pb(II), Cu(II), and Ni(II) under various conditions. Elemental compositions obtained with elemental dispersion X-ray (EDX), Fourier transform infrared (FTIR) spectra of expected functional groups, surface morphology, and high crystalline X-ray diffraction (XRD) confirmed the fabrication of TiO2/PKSAC/Fe3O4 composite. After a preliminary screening of the adsorbent loading (0.1 – 1.0 g L-1), operating parameters such as the initial concentration of metal ions (10 – 50 ppm) and the catalyst weight ratio (TiO2/PKSAC/Fe3O4; 1:1:1, 1:2:1, 2:1:1) were investigated to optimize the removal of metal ions. An optimal adsorbent dosage of 0.9 g L-1 allowed >80% removal efficiency in 10 ppm of mixed metal ions solution. Among all three catalyst ratios, the equivalent mass ratio of 1:1:1 (TiO2/PKSAC/Fe3O4) demonstrated the best performance (>72%) in removing Pb(II), Cu(II), and Ni(II) ions, even after the addition of coexisting ions (Ca2+, Na+, Cl-, and Br-) in the treatment mixture. A recycling study performed up to the fourth cycle confirmed the regenerative stability of TiO2/PKSAC/Fe3O4 composite. The fabricated TiO2/PKSAC/Fe3O4 composite can be applied as an appealing alternative technology and environmentally friendly material for multi heavy metals removal in wastewater.